USAHA KEPALA MADRASAH TSANAWIYAH NEGERI (MTSN) BATUSANGKAR SEBAGAI SUPERVISOR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Khairul Muslim (al-fikrah: Jurnal Manajemen Pendidikan, 2018)
This research begins of MTsN Batusangkar ranked champion always gets the best madrasah in Tanah Datar, both in terms of teacher quality, student quality and performance improvement headmaster, this is evidenced by the many accomplishments achieved by the madrasah. Both at the distric until province. This research is a qualitative research. Sources of primary data in this study is the head master of MTsN Batusangkar. Secondary data sources in this research is the Deputy Head Master, Head of Administration, teachers and students MTsN Batusangkar Tanah Datar District. Data collected by observation, interview and and document. The Data collection is done by the following steps, namely: data collection, data reduction, data display that has been analyzed and conclusions.The results of this study were, Planning of Head Master MTsN Batusangkar as a supervisor in improving the quality of learning is to plan the preparation of the program in one semester or yearly. The program is not overly rigid, depending on the number of teachers who need to be supervised. And also make a list of useful checklist sheet to check the completeness of the administration of learning tools for teachers. The Head Master of MTsN implementation Batusangkar as a supervisor in improving the quality of learning is to conduct supervision of the implementation of education, that there are three forms of the implementation of educational supervision conducted by the Head MTsN Batusangkar namely planning, classroom observation and evaluation as individual talks, and a teachers' meeting. The evaluation forms of the Head MTsN Batusangkar as a supervisor in improving the quality of teaching is that through the stages of individual talks and a teachers' meeting.